1404 NELA Risk Mortality Scores from Admission to Theatre in Emergency Gastrointestinal Perforation – A Retrospective Cohort Study. (12th October 2021) - Misbert, E; Hughes, M; Burke, J; Schofield, C; Young, A
Abstract: Background: Patients with acute abdominal pathology requiring emergency laparotomy who experience a delay to theatre have an increased risk of morbidity, mortality and complications. The aim of this study was to assess delay, from symptom onset to theatre in patients with gastrointestinal perforation and its effect on perioperative risk. Method: A single-centre retrospective study was performed in the Leeds Trust Hospitals, UK investigating the NELA database for patients requiring emergency laparotomy for perforated gastrointestinal viscus who presented to the acute surgical unit or emergency department between 1 st February 2018 and 31 st January 2020. Results: 101 patients met the inclusion criteria (47% F and 53% M), mean age 59 [21-91]. 37% of patients' NELA scores worsened from admission to pre-op (median change of + 5.9% IQR 1.3-11.5]), 14% stayed the same and 49% improved (median change of -4.4%[IQR 0.4-9.1]) 3% had their NELA score documented at the time of consent. 18% did not wait for a CT report or went straight to theatre. Mean time from admission to scan report was 9.3 hours (0.9-22.0). Median time from symptom onset to presentation (2 days [IQR 1-13]) was greater in patients with an Index of Multiple Deprivation Decile of 1-5, (n = 64, median 2 days [IQR 1-6]) compared to those in deciles 6-10, (n = 37, median 1 day[IQR 1-3]), p = 0.097. Conclusions: NELA mortality risk score changes from presentation to surgery in patients with acute gastrointestinal perforation requiring emergency laparotomy. There is suggestion that delay in symptom onset to presentation may correlate with Index of Multiple Deprivation Decile.